The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1186/s12909-021-02786-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of dyad versus individual simulation-based training on stress, anxiety, cognitive load, and performance: a randomized controlled trial

Abstract: Background Dyad learning has been shown to be an effective tool for teaching procedural skills, but little is known about how dyad learning may impact the stress, anxiety, and cognitive load that a student experiences when learning in this manner. In this pilot study, we investigate the relationship between dyad training on stress, anxiety, cognitive load, and performance in a simulated bradycardia scenario. Methods Forty-one fourth-year medical sc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…Working in pairs in this setting has been shown to permit more efficient use of simulators, is more cost‐effective than individual practice, and in the case of laparoscopic cholecystectomy, reduces surgical operating time (Kowalewski et al, 2019 ). Notably, dyad training for procedural skills has also been shown to significantly reduce stress and anxiety among students while learning (Abbott et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Working in pairs in this setting has been shown to permit more efficient use of simulators, is more cost‐effective than individual practice, and in the case of laparoscopic cholecystectomy, reduces surgical operating time (Kowalewski et al, 2019 ). Notably, dyad training for procedural skills has also been shown to significantly reduce stress and anxiety among students while learning (Abbott et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many valued the ability to independently problem solve, aligning with the findings of Abbott et al, who found that although DP participants reported lower stress and anxiety, a majority still preferred IP. 28 The remaining major themes describe disadvantages of IP: limitations of a lack of peer-to-peer support and teamwork, learning being restricted due to the lack of peer feedback, and limitations of continuous repetitive practice. Whilst some participants valued independence, others recognized the inefficiency of continuous repetitive practice, as they were limited to their own abilities which are less than the shared abilities of a collaborative pair.…”
Section: Discussionmentioning
confidence: 99%
“…Abbott et al (2021) compared dyad versus individual simulation-based training on performance. Dyad practicing caused similar performance versus solo training [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of their phenomenological research indicated that the student’s level of self-efficacy increased as a result of interactions with their peers [ 32 ]. In addition, some studies indicated a decrease in the student dyads’ level of anxiety and stress and increased confidence in their abilities [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%